Ultrastructural and dynamic studies of the endosomal compartment in Down syndrome - Botté, Alexandra (2021)
Enlarged early endosomes have been visualized in Alzheimer's disease (AD) and Down syndrome (DS) using conventional confocal microscopy at a resolution corresponding to endosomal size (hundreds of nm). In order to overtake the diffraction limit, we used super-resolution structured illumination microscopy (SR-SIM) and transmission electron microscopies (TEM) to analyze the early endosomal compartment in DS.By immunofluorescence and confocal microscopy, we confirmed that the volume of Early Endosome Antigen 1 (EEA1)-positive puncta was 13-19% larger in fibroblasts and iPSC-derived neurons from individuals with DS, and in basal forebrain cholinergic neurons (BFCN) of the Ts65Dn mice modelling DS. However, EEA1-positive structures imaged by TEM or SR-SIM after chemical fixation had a normal size but appeared clustered. In order to disentangle these discrepancies, we imaged optimally preserved High Pressure Freezing (HPF)-vitrified DS fibroblasts by TEM and found that early endosomes were 75% denser but remained normal-sized.RNA sequencing of DS and euploid fibroblasts revealed a subgroup of differentially-expressed genes related to cargo sorting at multivesicular bodies (MVBs). We thus studied the dynamics of endocytosis, recycling and MVB-dependent degradation in DS fibroblasts. We found no change in endocytosis, increased recycling and delayed degradation, suggesting a "traffic jam" in the endosomal compartment.Finally, we show that the phosphoinositide PI (3) P, involved in early endosome fusion, is decreased in DS fibroblasts, unveiling a new mechanism for endosomal dysfunctions in DS and a target for pharmacotherapy.